2004
DOI: 10.1111/j.0303-6979.2004.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐based assessments of clinical periodontal conditions in relation to alveolar bone loss

Abstract: The number of teeth lost and the proportion of plaque scores provided significant predictive factors for ABL. The functional PPRD demonstrated an exclusive and highly predictable association with ABL. Subject-based proportional data for PDs >4.0 mm provided poor substitute measures for the extent of ABL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…6 cross‐sectional studies were also identified (Persson et al. 2003b, Renvert & Persson , Chandra , Trombelli et al. , Eshwar et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 cross‐sectional studies were also identified (Persson et al. 2003b, Renvert & Persson , Chandra , Trombelli et al. , Eshwar et al.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve publications reported on the Periodontal Risk Assessment (PRA) and its modifications (Lang & Tonetti , Persson et al. 2003c, Renvert & Persson , Chandra , Eickholz et al. , Jansson & Norderyd , Eshwar et al.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is well known that poor oral hygiene, advancing age, and tobacco habits (such as cigarette smoking and tobacco chewing) are significant risk factors of alveolar bone loss. [42][43][44][45][46] Because all studies [22][23][24][25]27,28 including in this systematic review were performed in animals, it remains to be determined whether or not VD3 supplementation would facilitate new bone formation in elderly individuals (.65 years old), patients with a poor plaque control and habitual tobacco product users. It is postulated that the outcomes of VD3 supplementation therapy in terms of augmenting new bone formation around implants are compromised in vulnerable populations (such as patients with a poor plaque control, habitual tobacco product users, and elderly individuals).…”
Section: Discussionmentioning
confidence: 99%
“…and included in several multifactorial risk models. [43][44][45] All criteria were selected on the basis that long-term studies conclude that there is good to fair evidence that each is associated with a patient's susceptibility to progression of PDs.…”
Section: Resultsmentioning
confidence: 99%
“…Multifactorial risk assessment models such as the computer-based Periodontal Risk Calculator (PRC) developed by Page et al, 43 the Periodontal Risk Assessment (PRA) diagram developed by Lang and Tonetti,44 and modifications thereof by Renvert and Persson,45 combine varied data from an evaluation of many factors to determine risk. These include smoking behavior, systemic and genetic conditions, such as a diagnosis of diabetes mellitus and the availability of data indicating interleukin (IL)-1 gene polymorphism, the presence of specific pathogenic bacteria in the subgingival biofilm, and poor oral hygiene status.…”
Section: Multifactorial Risk Assessment Modelsmentioning
confidence: 99%